Common mental disorders in young refugees in Sweden: the role of education and duration of residency. (30th September 2020) - Mittendorfer Rutz, E; Helgesson, M; Norredam, M; Sijbrandij, M; Jamil de Montgomery, C; Björkenstam, E
Abstract: Background: Studies investigating risks of common mental disorders (CMDs) in refugee youth are sparse. The current study examined health care use due to CMDs in unaccompanied and accompanied refugee youth and Swedish-born, and the role of education and residency duration. Methods: This register-based, longitudinal cohort study included 743, 671 individuals (whereof 33, 501 refugees) between 19-25 years, residing in Sweden in 2009. Refugees were classified as unaccompanied/accompanied. Risk estimates of CMDs, measured as health care and antidepressant treatment, between 2010-2016 were calculated as adjusted hazard ratios (aHR) with 95% confidence intervals (CI). Highest attained education in 2009, and residency duration were examined as potential modifiers. Results: Compared to Swedish-born youth, refugees had a lower risk of treated major depressive and anxiety disorders (aHR): 0.73 (95% CI 0.68-0.78) and 0.74 (95% CI 0.70-0.79) respectively), but a higher risk for posttraumatic stress disorders (PTSD). Compared to Swedish-born, unaccompanied had an 8-fold elevated risk for PTSD (aHR: 8.40, 95% CI 6.16-11.47) and accompanied refugees had a nearly 3-fold risk of PTSD (aHR: 2.78, 95% CI 2.29-3.37). Rates of PTSD decreased with years spent in Sweden. The risk of CMDs decreased with increasing education. Conclusions: Young refugees had a lower risk of treated depressive and anxiety disorders, but a higher risk for PTSD. In refugees, the rates of anxiety disorders increased slightly over time, whereas the rates of PTSD decreased. Last, low education was an important predictor for CMDs. Key messages: Our study highlights the need to specifically focus on stress-related mental disorders in studies on refugees as risk estimates might differ. Moreover, providing scalable low-intensity interventions to address CMDs including posttraumatic stress are an important first step in order to prevent prolonged suffering and persistence of PTSD in refugee youth.